Dynamika psaní na klávesnici v kombinaci s klasickými hesly - Hub, Miloslav (Univerzita Pardubice, 2004)
Authentification as a data security instrument in our informational society is very important for keeping yuor data as safe as possible. There are 3 types of authentification: authentification by knowledge, by subjekt and biometric authentification. Each one has both advantages and disadvantages. They can be combined to increase the security of your information as well. There are some ideas that suggests reasonable combination of password ans keystroke dynamic.
Keywords: psaní; dynamika; klávesnice; biometrika